(untitled) (Italian Journal of Public Health, 2010)
Background: The aim of this paper is to propose a risk based surveillance model for environmental pollutants, monitoring the presence and the quantity of toxic contaminants in cattle and sheep products. Methods: The province of Latina was chosen as study area. The official list of polluted sites was provided by the Province. This was then integrated into a Geographic Informative System together with geographical, hydrographic, and geological data along with information regarding the farms that was obtained from the National Livestock Registry. In order to identify the monitoring priority of polluted sites, a semi-quantitative risk assessment was then set up. A score for each of the attributes considered in the risk evaluation was given to each site, based on two main criteria: the environmental hazard characterization and the quantification of the exposed animal population. The sample of farms to be monitored was defined according to statistical criteria. Results: 12 polluted sites were chosen as “at major risk” among the 58 identified therefore, inside the respective surrounding risk areas, 24 farms were chosen to be monitored. Biological materials to be sampled were also defined. As a result, it was determined that 104 samples collected throughout a year would be sufficient to detect any contamination in the territory of the Province, with an admitted prevalence of 10% among farms at risk (CL 95%). Conclusions: Risk based surveillance is more sensitive in detecting environmental pollution than surveillance that is randomly performed, based on the same allocation of financial resources.